The Incorporation of Crumb Rubber in Construction Reinforcement: A Review - Januar, Parlaungan Siregar; Al Ichlas, Imran; Rozanna, Dewi; Janviter, Manalu; Johni Jonathan, Numberi; Apolo, Safanpo (INTI International University, 2023)
This study explores the use of rubber crumbs in construction materials, focusing on their impact on structural integrity, flexibility, crack resistance, and vibration dampening. The study highlights the environmental benefits of incorporating rubber crumbs into buildings, such as reducing waste tyre disposal. The study also examines the chemical composition, particle size, and physical properties of rubber crumbs, which significantly affect the mechanical, thermal, and elastic capabilities of various building materials. The study also investigates surface modifications made to rubber crumbs, examining their impact on performance, microstructure, and lifespan. The study also delves into the potential benefits of noise reduction, the development of ecologically sound concrete blocks, and the environmental sustainability and health issues associated with rubber crumbs. The study emphasizes the need to assess the entire lifespan and ecological effects of rubber crumbs treatments, emphasizing their positive effect on road clamping performance despite environmental limitations. Overall, the study highlights the importance of considering the entire lifespan and ecological effects of rubber crumbs in the construction industry.